Relazione dell'uficio anniversario fatto celebrare in Napoli nella Chiesa de' SS. Apostoli de' RR. C.R. Teatini, il dì XXVIII di novembre MDCCLII, per Diego Pignatelli di Aragona, duca di Terranova e Montelione - Cepparuli, Francesco.; Sesoni, Francesco, b. 1705.; Baldi, Antonio, 1692-ca. 1778; Porsile, Serafino.; Pignatelli di Aragona, Fabrizio, duca di Terranova e Montelione.; Caracciolo, Niccola, 18th cent. (In Napoli : Per Serafino Porsile ., 1753)
Plated printed in green. Title printed in red and green; title vignette; head- and tail-pieces; decorative initials. "Oratione di Niccola Caracciolo . a lode di Diego Pignatelli .: p. [I]-XXXIV. Frontispiece portrait of Diego Pignatelli, engraved by Antonio Baldi after Domenico Mondo; other plates are engraved by Francesco Sesoni and Francesco Cepparuli. Final page blank. Errata: p. [1] at end. Publication date from privilege statement. Mode of access: Internet. Bound in red goatskin; boards gilt tooled with panel design composed of fillets, rolls and stamped corner ornaments built up with small tools; decorated pastedown paper in gold and purple; edges mottled green; armorial bookplate on front pastedown.